1995
DOI: 10.1055/s-2007-979588
|View full text |Cite
|
Sign up to set email alerts
|

Microstate Segmentation of Spontaneous Multichannel EEG Map Series under Diazepam and Sulpiride

Abstract: Spontaneous multichannel brain electric field (EEG) map series of 20 seconds duration at 1, 15, 30, 45, and 60 minutes after the injection of a single dose of diazepam (13 ss) or sulpiride (6 ss) were segmented into microstates of quasi-constant landscape but varying durations. Post-minus-preinjection difference values were computed for the six microstate variables: specific window size, duration, orientation, distance between windows, and location of center of gravity on the anterior-posterior and left-right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…In the present review, we focus on those studies that used k-mean cluster analysis to determine the number of microstates and those that fixed the number of states to the canonical four maps. Earlier studies using different approaches for analysis (Dierks et al, 1997;Kinoshita et al, 1995;Strik et al, 1997;Strik et al, 1995) are not listed. The most prominent pathology studied using this approach is schizophrenia.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In the present review, we focus on those studies that used k-mean cluster analysis to determine the number of microstates and those that fixed the number of states to the canonical four maps. Earlier studies using different approaches for analysis (Dierks et al, 1997;Kinoshita et al, 1995;Strik et al, 1997;Strik et al, 1995) are not listed. The most prominent pathology studied using this approach is schizophrenia.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In addition, the observed microstate configurations were concentrated in a few classes of field configurations which can be identified by spatial clustering [22,23] . Microstates have been studied for human information processing in healthy subjects [24,25] . Abnormal patterns of microstates have been reported in patients with dementia of the Alzheimer type who are characterized by cognitive impairments [26] .…”
Section: Introductionmentioning
confidence: 99%
“…This approach implies a virtually unlimited time resolution (time-sample-bytime-sample decisions) and is therefore most appropriate for studies on brain information processing because these latter operations occur in the millisecond to sub-second range. Several studies on spontaneous Wackermann et al, 1993;Kinoshita et al, 1995) as well as event-related data (Lehmann and Skrandies, 1980;Brandeis et al, 1995;Koenig and Lehmann, 1996) showed that the field configuration changes in a clearly discontinuous way within a sub-second time range: brief epochs of quasi-stable field topography are concatenated by rapid changes of the spatial configuration. Algorithms that parse the sequences of momentary field maps into time segments of stable topography reduce these map series into sequences of microstates.…”
Section: Introductionmentioning
confidence: 99%